Effects of playing surface (hard and clay courts) on heart rate and blood lactate during tennis matches played by high-level players - Martin, C.; Thevenet, D.; Zouhal, H.; Mornet, Y.; Delès, R.; Crestel, T.; Ben Abderrahman, A.; Prioux, J. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to compare tennis matches played on clay (CL) and resin (R) courts. Six matches were played (3 on CL courts and 3 on R courts) by 6 high-level players. Heart rate (HR) was monitored continuously while running time (4.66 m), and blood lactate concentration ([La]) were measured every 4 games. Mean duration of points and effective playing time (EPT) were measured for each match. Mean HR (154 ± 12 vs. 141 ± 9 b/min) and [La] values (5.7 ± 1.8 vs. 3.6 ± 1.2 mmol/L) were significantly higher on CL (p < 0.05). The [La] increased significantly during the match on CL court. Mean duration of rallies (8.5 ± 0.2 vs. 5.9 ± 0.5 seconds) and EPT (26.2 ± 1.9 vs. 19.5 ± 2.0%) were significantly longer (p < 0.05) on CL. Running time values in speed tests were not significantly different between CL and R. Running time performance was not significantly decreased during the match, whatever the playing surface. This study shows that the court surface influences the characteristics of the match and the player's physiological responses. The court surface should be a key factor for consideration when coaches determine specific training programs for high-level tennis players.